Aerobic Training Prevents Dexamethasone-Induced Peripheral Insulin Resistance - Dionísio, T. J.; Louzada, J. C. A.; Viscelli, B. A.; Dionísio, E. J.; Martuscelli, A. M.; Barel, M.; Perez, O. A. B.; Bosqueiro, J. R.; Brozoski, D. T.; Santos, C. F.; Amaral, S. L. (Hormone and Metabolic Research, 2014)
This study investigated how proteins of the insulin signaling cascade could modulate insulin resistance after dexamethasone (Dexa) treatment and aerobic training. Rats were distributed into 4 groups: sedentary control (SC), sedentary+Dexa (SD), trained control (TC), and trained+Dexa (TD), and underwent aerobic training for 70 days or remained sedentary. Dexa was administered during the last 10 days (1 mg · kg−1 per day i. p.). After 70 days, an intraperitoneal glucose tolerance test (ipGTT) was performed. Protein levels of IRS-1, AKT, and PKC-α in the tibialis anterior (TA) muscle were identified using Western blots. Dexa treatment increased blood glucose and the area under the curve (AUC) of ipGTT. Training attenuated the hyperglycemia and the AUC induced by Dexa. Dexa reduced IRS-1 (− 16%) and AKT (− 43%) protein level with no changes in PKC-α levels. Moreover, these effects on IRS-1 and AKT protein level were prevented in trained animals. These results show for the first time that aerobic exercise prevented reductions of IRS-1 and AKT level induced by Dexa in the TA muscle, suggesting that aerobic exercise is a good strategy to prevent Dexa-induced peripheral insulin resistance.
Keywords: glucocorticoids; insulin cascade pathway; aerobic exercise training; skeletal muscle